ENERGY AND EXERGY EVALUATION OF A 220MW THERMAL POWER PLANT (Nigerian Journal of Technology, 2017)
A component based energy and exergy evaluation was performed on a 220MW thermal power plant in Nigeria. The component based exergy analysis examines and compares the energetic and exergetic performances of each component by identifying the deficiencies of each component. Design and operating data were obtained from Egbin power plant in Nigeria. The result of the analysis showed that the total exergy that was destroyed in the power plant was 400.015 MW.  The major contributors to the exergy destruction in the power plant were the boiler (87%), the three turbines (a combined total of 9%) and the condenser (2 %).The effect of increasing the  High Pressure turbine (HPT) inlet temperature at constant boiler pressure incresses the exergy efficiency of the component as well as the second law efficiency of the power plant, thus  reducing the exergy destruction of the component. At the variation of environmental or dead state temperature, there were no appreciable changes in the values of exergy efficiency of the boiler/steam generator. The outcomes of this work provide the exergy consumption and distribution profiles of the thermal power plant, making it possible to adopt effective energy-saving measures.http://dx.doi.org/10.4314/njt.v37i1.15